Role of Lactobacillus in cervical cancer - Yang X (Cancer Management and Research, 2018)
Xi Yang,1 Miao Da,2 Wenyuan Zhang,3 Quan Qi,4 Chun Zhang,5 Shuwen Han4 1Department of Intervention and Radiotherapy, Huzhou Central Hospital, 2Medical College of Nursing, Huzhou University, 3Department of Gynaecology, 4Department of Medical Oncology, 5Department of Infectious Diseases, Huzhou Central Hospital, Huzhou, Zhejiang Province, People’s Republic of China Abstract: Cervical cancer is a common malignant cancer among women worldwide. Changes in the vaginal microecological environment lead to multiple gynecological diseases, including cervical cancer. Recent research has shown that Lactobacillus may play an important role in the occurrence and development of cervical cancer. This review explores the role of Lactobacillus in cervical cancer. A total of 29 articles were included after identification and screening. The pertinent literature on Lactobacillus in cervical cancer from two perspectives, including clinical studies and experimental studies, was analyzed. An association network for the mechanism by which Lactobacillus induces cervical cancer was constructed. In addition, we provide direction and insight for further research on the role of Lactobacillus in cervical cancer. Keywords: CIN, cervical cancer, Lactobacillus, microorganism